Coronary arteriovenous malformation, as imaged with cardiac computed tomography angiography: A case series - Khachatryan, Tigran (EduRad, 2010)
INTRODUCTION: Coronary Arteriovenous Malformations (AVM) can lead to various cardiovascular events. The severity of clinical manifestation depends on the degree of the malformation. The significance of major arterial shunt is that they can deprive the myocardium of the necessary amount of blood, leading to myocardial ischemia, and potentially tachycardia, left ventricular dilatation and heart failure secondary to increased stroke volume and cardiac output. Cardiac computed tomography (CCT) has proven to be a good non-invasive diagnostic tool in the detection of coronary Arteriovenous Malformations. CASE PRESENTATION: We include 4 patients, who presented with various symptoms in relation to the coronary Arteriovenous Malformations. Diagnostic confirmation was made non-invasively using multi-row detector cardiac computed tomography (MDCT). CONCLUSION: Coronary Arteriovenous Malformation is a rare congenital disease which can produce symptoms of varying severity depending on the size of the malformation. CCT angiography can help in non-invasively diagnosing the malformation along with revealing the anatomic details, which can be used for surgical planning, or for better medical management of the patients.